All-Fiber Tunable LP11 Mode Rotator With 360° Range - Zhikun Hong; Songnian Fu; Dawei Yu; Ming Tang; Deming Liu (IEEE Photonics Journal, 2016)
We propose and experimentally demonstrate an all-fiber tunable ${\rm{LP}}_{11}$ mode rotator with 360° range, based on the bending and twisting of the two-mode fiber (TMF). A theoretical model of TMF perturbation and its effect on the spatial pattern of ${\rm{LP}}_{11}$ mode is put forward. We experimentally characterize the implementation of the ${\rm{LP}}_{11}$ mode rotator by an all-fiber polarization controller configuration. The results agree well with the theoretical investigations. We are able to demonstrate arbitrary ${\rm{LP}}_{11}$ mode rotation with 360° range. The insertion loss is less than 0.4 dB when the operation wavelength is varied from 1540 to 1560 nm.